Enhancing Public Understanding of Self-Medication through The Android-Based “E-Farmasi” Application at Alif Pharmacy, Sidrap Regency - Shabran Hadiq; Dewi Lidiawati; Reny Anggriany Hakim; Hasrul Hasrul (Universitas Ngudi Waluyo, 2025)
Self-medication is defined as the practice of treating minor ailments without a doctor’s prescription, which, if not carried out properly, may pose significant health risks. A lack of understanding regarding the appropriate use of medicines remains a major challenge in self-medication practices. This study aims to analyze the effect of utilizing the Android-based “E-Farmasi” application on public understanding of self-medication, implemented at Alif Pharmacy, Sidrap Regency. The research employed a quantitative approach with a quasi-experimental method, using a pretest–posttest design involving 53 respondents who met the inclusion and exclusion criteria. The results demonstrated that the mean understanding scores of respondents before and after the intervention were 7.00±0.94 and 9.21±0.99, respectively, with a p-value of 0.000 < 0.05 based on the Wilcoxon Signed Rank Test. These findings indicate a significant effect on respondents’ understanding of independent medication use after utilizing the application. The educational and interactive features of “E-Farmasi” proved effective in providing accurate and easily accessible information regarding drug types, dosages, and side effects. This study recommends further development of the application as a practical and modern public health education strategy, with future research conducted across multiple pharmacies.